Corruption Scandals as Engines of Systemic Change: The Case of MG Baltic - Lašas, Ainius; Jankauskaitė, Vaida (Politologija, 2019)
[full article and abstract in Lithuanian; abstract in English]This article aims to determine the impact of corruption scandals on systemic partisan and legislative changes. The study is based on one case analysis focusing on the MG Baltic corruption scandal, which can be distinguished from other corruption scandals by its systemic large-scale trade of and the impact on political processes in Lithuania. The study uses the triangulation method using both official sources of information and 15 anonymous interviews that helped measure changes in informal politics-business relations in the context of the MG Baltic scandal. The changes are analyzed on three levels: changes in legislation, prevention of corruption within parties, and changes in informal political routines. The analysis confirms the significance of the three variables examined in the study – public discontent, media attention and political leadership – for the implementation of anti-corruption reforms.
Keywords: corruption; corruption scandals; political parties; business